Curating live arts : critical perspectives, essays, and conversations on theory and practice - Davida, Dena; Gabriels, Jane; Hudon, Véronique; Pronovost, Marc (New York : Berghahn Books, 2019)
"Situated at the crossroads of performance practice, museology, and cultural studies, live arts curation has grown in recent years to become a vibrant interdisciplinary project and a genuine global phenomenon. Curating Live Arts brings together bold and innovative essays from an international group of theorist-practitioners to pose vital questions, propose future visions, and survey the landscape of this rapidly evolving discipline. Reflecting the field's characteristic eclecticism, the writings assembled here offer practical and insightful investigations into the curation of theatre, dance, sound art, music, and other performance forms--not only in museums, but in community, site-specific, and time-based contexts, placing it at the forefront of contemporary dialogue and discourse"--
From context to concept: the emergence of the performance curator / Bertie Ferdman -- Exhibiting performances, process and valorisation: When Attitudes Become Forms: Bern 1969/ Venice 2013 / Beatrice von Bismarck -- Can we curate dance without making a festival?: on dance curatorship and its shifting borders / Elisa Ricci -- What curating can offer performance in Africa or the aftermath of an interview with Jareh Das / 'Funmi Adewole, with Jareh Das -- The curating nation: development of performance curation in Singapore and its impact on regional cultural politics / Ken Takiguchi -- The curatorial chronotope / Peter Dickinson -- More weirdness, more joy: performance curation and pedagogy at Danspace Project and the Institute for Cultural Practice in Performance / Judy Hussie-Taylor -- Dancing the museum / Thomas F. DeFrantz -- Curatorial discourse and equity: tensions in contemporary dance presenting in the United States / Naomi M. Jackson -- Noticing the feedback: a proposal to the contemporary dance field, and/or this revolution will be crowdsourced / Michèle Steinwald -- Email to a curator: an introduction to The Curator's Piec / Tea Tupajić and Petra Zanki -- Curation as a form of artistic practice: context as a new work through UK-based Forest Fringe / Deborah Pearson -- The artist-curator, or the philosophy of 'do-it-yourself / Julie Bawin -- Being in vanguard of sensibility: artists as curators in performing arts: a study of collective affect / Kasia Tórz -- Familias: artist-activist curation in the South Bronx, New York / Jane Gabriels -- What we talk about when we talk about curating the 'unexpected / Syreeta McFadden -- Because I love art, I want art to be different: the project Perverse Curating and a few things I've learned from it / Jacob Wren -- Making stage: contemporary dance and performance curation in the Caribbean / Makeda Thomas -- The work of the musician-curator in relation to of the 'Concert Scenario' / Marie-Hélène Breault -- Pseudo-, anti-, and total dance: a self-interview on curation / Salta -- Collective creation and improvised curation: a discussion with the Body Slam / Body Slam Dance Improv Collective: Gregory Selinger, Helen Simard, Roger White, Xavier Laporte, Victoria Mackenzie, and Claudia Chan Tak -- A new kind of critical elsewhere / Travis Chamberlain -- Re-enact history? Performing the archive! / Julia Kurz -- Choreographing archives, curating choreographers: the dance retrospective / Fabien Maltais-Bayda and Joseph Henry -- Exhibiting dance, performing objects: cultural mediation in the museum / Erin Joelle McCurdy -- The curator's work: stories and experiences of Tino Sehgal's Events / Véronique Hudon -- Framing a network, charting dis/courses: performance curation, community work and the logic/anxieties of an emerging field / Roselle Pineda -- Food=Need: constraints, reflexivity and community performance / Pam Patterson -- ARC.HIVE of contemporary Arab performing arts: memory, catastrophe, resistance and oblivion / Adham Hafez -- Collective Walks/ Spaces of Contestation: site-specificity, community involvement and mobility employed as curatorial strategies in the creation of participatory performances / Mariane Bourcheix-Laporte -- Sound citizen: curating sound art in the distributed public sphere / Morten Søndergaard -- Rethinking the role of institutions and curators in a new interdisciplinary age / Philip Bither -- The curator as a culture producer / Marta Keil -- How to build a manifesto for the future of a festival "Festivals as thinking entities," a conversation with Judith Blackenberg, Daniel Blanga-Gubbay, Silvia Bottiroli and Berno Odo Polzer / Silvia Bottiroli -- The curatorial gesture as a decolonial gesture / Arnaldo Rodriguez Bagué -- Are you not entertained? Curating performance within the institution / Rie Hovmann Rasmussen -- Bodies in museums: institutional practices and politics / Véronique Hudon with Boris Charmatz -- What can contemporary art perform? And then transgress? / Emelie Chhangur -- Situation critical: what comes next for the field of performance curation? / Tom Sellar
Includes bibliographical references and index
Description based on print version record
eBooks on EBSCOhost
Keywords: Performing arts archives; Archives des arts du spectacle; SPORTS & RECREATION / General; PERFORMING ARTS / General; Performing arts archives; Curatorship; Performing arts